Strategies for development of STEM competencies of new generation future specialists - Dulatkyzy, D.; Akbayeva, G.N.; Romanenko, S.V. (Karagandy University of the name of acad. E.A. Buketov, 2025)
In the rapidly changing landscape of the 21st century, proficiency in Science, Technology, Engineering, and Mathematics (STEM) has become essential for the future workforce. This research focuses on examining the development of STEM competencies in upcoming professionals through effective approaches, specifically the inquiry-based learning (IBL) strategy. The investigation delves into successful strategies for cultivating STEM skills in the next generation of experts, highlighting the significance of inquiry-based teaching strategy. The paper also examines the role of students and educators in creating an environment conducive to STEM competency development. By aligning educational practices with the demands of the modern workforce, these strategies aim to produce adaptable, innovative, and skilled professionals capable of addressing global challenges and driving sustainable progress. This program demonstrates how inquiry-based learning method can effectively impact on the new generation of future specialists. The study emphasizes the importance of an inquiry-based learning strategy for the development of STEM competencies, which enhances educators’ and students’ practical skills as well as their readiness to study and assume personal accountability for their education. The findings demonstrated that by enhancing their STEM knowledge and competencies, the IBL strategy program benefited both educators and students.
Жаңа буын болашақ мамандарының STEM-құзыреттіліктерін дамыту стратегиялары
Стратегии развития STEM-компетенций будущих специалистов нового поколения
Keywords: STEM competencies; IBL strategy program; key strategies; development; students; educators; future specialists of new generation; educational practice